2010
DOI: 10.1182/blood-2009-10-247361
|View full text |Cite
|
Sign up to set email alerts
|

Transformation by Tribbles homolog 2 (Trib2) requires both the Trib2 kinase domain and COP1 binding

Abstract: Tribbles homolog 2 (Trib2) is a pseudokinase that induces acute myelogenous leukemia (AML) in mice and is highly expressed in a subset of human AML. Trib2 has 3 distinct regions, a proline-rich N-terminus, a serine/threonine kinase homology domain, and a C-terminal constitutive photomorphogenesis 1 (COP1)-binding domain. We performed a structure-function analysis of Trib2 using in vitro and in vivo assays. The N-terminus was not required for IntroductionTribbles (Trib) pseudokinases have recently emerged as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
149
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(157 citation statements)
references
References 37 publications
5
149
2
Order By: Relevance
“…One explanation may be that the protein complexes containing TRIB2 and C/EBPα p42 or TRIB2 and p30 are different. Our previous work showed that TRIB2 binds with COP1 E3 ligase and this interaction is necessary for C/EBPα p42 degradation (13). While our peptide mapping clearly shows specific sites in both TRIB2 and C/EBPα responsible for the direct interaction, in the absence of crystal structure information we cannot predict further based on our data the reason why p30 is not targeted by TRIB2 for degradation.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…One explanation may be that the protein complexes containing TRIB2 and C/EBPα p42 or TRIB2 and p30 are different. Our previous work showed that TRIB2 binds with COP1 E3 ligase and this interaction is necessary for C/EBPα p42 degradation (13). While our peptide mapping clearly shows specific sites in both TRIB2 and C/EBPα responsible for the direct interaction, in the absence of crystal structure information we cannot predict further based on our data the reason why p30 is not targeted by TRIB2 for degradation.…”
Section: Discussioncontrasting
confidence: 71%
“…In this study we identify the molecular mechanism involved in the dysregulation of C/EBPα expression via TRIB2 in AML. We and others (10,13,30) have previously demonstrated that TRIB2 overexpression induces AML and that it degrades C/EBPα p42. Here we provide novel insights on this process and show that the presence of C/EBPα p42 is required not only to initiate TRIB2 AML, but also for TRIB2 to cooperate with C/EBPα (p42 loss and increased p30) in driving AML disease.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the cytoplasm, Tribs direct the proteosomal degradation of key signaling proteins, including ACC1 (Qi et al, 2006), SMURF1, FoxO (Matsumoto et al, 2006) and C/ EBP Naiki et al, 2007;Selim et al, 2007;Dedhia et al, 2010;Keeshan et al, 2010;Grandinetti et al, 2011). Also in the cytoplasm, Tribs bind to inactivate LAP (Naiki et al, 2007), MKKs (Kiss-Toth et al, 2004;Wang et al, 2011), and Akt (Du et al, 2003).…”
Section: Subcellular Localization Of Tribsmentioning
confidence: 99%